Public sewage wastewater treatment by using electrocoagulation process - Noor Suwaibah, Hamdan (2010)
Sewage wastewater is polluted and it can be treated by using the method of electrocoagulation process. The electrocoagulation process is one of the methods to clean the sewage wasteWater. Sewage wastewater characteristic can be divided into three major categories which are physical, chemical, biological, and chemical The primary objective of this study are to characterize the sewage waste water properties in terms of the BOD COD, SS and the pH affluence before and after the sample is being treated by the electrocoagulation process and to determine the effect of ampere through the process and the sewerage properties that involve. There are five parameter experiments that has been done to determine the quality of the effluent which are biochemical oxygen demand (BOD), chemical oxygen demand (COD), suspended solid (SS), pH and the gases that produce. From the experiment, the reading of the BOD, COD, SS, pH and gases are within the as stated in table 4.1 42, and 4.3. Based on the results the sewage wastewater quality is compare according to the standard that stated in the Environmental Quality Act (Sewage and Industrial Effluents) Regulations 1979, Maximum Effluent Parameter Limit Standard A and B as stated in appendix A. The sewage wastewater condition result after treated was filling up the standard which is fixed by and the result was based on the ampere effect through the electrocoagulation process to the sewage wastewater, This is show that the sewage wastewater can be treated by using the electrocoagulation process.